FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISMENOREA PADA MAHASISWI STIKES TRI MANDIRI SAKTI KOTA BENGKULU - Suryani - Suryani (STIKes CHMK, 2020)
Dysmenorrhoea (painful menstruation) is pain during menstruation. Dysmenorrhoea consists of complex symptoms in the form of lower abdominal cramps that spread to the back or legs and are usually accompanied by gastrointestinal symptoms and neurological symptoms such as general weakness. This study aims to study the factors associated with the incidence of dysmenorrhoea in STIKES Tri Mandiri Sakti Bengkulu City students. This type of research is an analytic survey using a cross sectional design. The population in this study were all female students of the 2018/2019 academic year. The sampling technique in this study used Simple Random Sampling and obtained a sample of 56 respondents. Data analysis techniques were performed using univariate and bivariate analysis with the Chi-Square Test. The results obtained from 56 respondents showed that 73.2% of respondents experienced dysmenorrhoea, 66.1% of respondents had less knowledge, 73.2% of respondents did not carry out regular exercise habits, 60.7% of respondents often did the habit of eating fast food and 69.6% of respondents have a family history. The results showed that there was a relationship between knowledge and family history with dysmenorrhoea in STIKES Tri Mandiri Sakti Bengkulu City students. Factors that are not related to dysmenorrhoea are sporting habits and eating fast food habits among STIKES Tri Mandiri Sakti Bengkulu City students. The results of this study are expected to increase knowledge about reproductive health, especially dysmenorrhoea so that the events experienced can be handled properly.